The role of social enterprise as a panacea in the capitalist systemargues - Mohd Radzi, Naziatul Aziah; Saidi, Normaizatul Akma; Mohd Ali, Ahmad Fahme (Universiti Teknologi MARA, Terengganu, 2022)
We have always encountered the phrase “capitalist economic system” in the media and perhaps in our previous education. What does the capitalist economic system refer to? The system is easily characterised by free markets and minimal or no government intervention in the economy. The system is typified by economic freedom, in which there are no restrictions on individuals who wish to establish a business and provide the goods and services they desire; and consumer sovereignty, in which consumers are free to choose which products to purchase and which services to obtain. Aside from this, government intervention is non-existent or minimal, and business is based solely on profit, market forces, elastic labour markets, and free trade.